1998
DOI: 10.1002/(sici)1097-0185(199810)252:2<159::aid-ar1>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Topographical distribution of cells in the rat submandibular gland duct system with special reference to dark cells and tuft cells

Abstract: The duct system of the rat submandibular gland consists of the intercalated duct, the granular convoluted tubule, the striated duct, the excretory duct, the main excretory duct, and the salivary bladder. The duct system contains special cell types, such as dark cells and tuft cells, in addition to principal cells. However, little is known about cell distribution in the duct system. The purpose of the present study was to examine cell distribution and to perform a morphometric analysis of the duct system. Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Sbarbati and Osculati (2005) have recently carried out an extensive survey of the same cell type referred to as brush cells. In the digestive tract, tuft cells are present in the salivary duct (Shackleford & Schneyer, 1971;Sato, 1980Sato, , 1982Hand, 1981;Sato & Miyoshi, 1988;Higashi et al, 1989;Sato & Miyoshi, 1996, 1998aSato et al, 1998Sato et al, , 2000Sato et al, , 2002Sato et al, , 2004, stomach (Hammond & LaDeur, 1968;Isomäki, 1973;Wattel & Geuze, 1978;Luciano et al, 1980;Luciano & Real, 1992;Luciano et al, 1993;Kugler et al, 1994;Luciano et al, 2003), gallbladder (Luciano & Real, 1969, 1990Nevalainen, 1977;Luciano et al, 1981), common bile duct (Riches, 1972;Luciano et al, 1981;Iseki, 1991), small and (Trier, 1963;Silva, 1966;Schofield, 1970;Nabeyama & Leblond, 1974;Tsubouchi & Leblond, 1979;Sugimoto et al, 1983;Trier et al, 1987;Gebhard & Gebert, 1999;Wille, 2001), and pancreatic duct (Weyrauch & Schnorr, 1976;Kugler et al, 1994;. Such cells have also been repo...…”
Section: Distribution Of Tuft Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sbarbati and Osculati (2005) have recently carried out an extensive survey of the same cell type referred to as brush cells. In the digestive tract, tuft cells are present in the salivary duct (Shackleford & Schneyer, 1971;Sato, 1980Sato, , 1982Hand, 1981;Sato & Miyoshi, 1988;Higashi et al, 1989;Sato & Miyoshi, 1996, 1998aSato et al, 1998Sato et al, , 2000Sato et al, , 2002Sato et al, , 2004, stomach (Hammond & LaDeur, 1968;Isomäki, 1973;Wattel & Geuze, 1978;Luciano et al, 1980;Luciano & Real, 1992;Luciano et al, 1993;Kugler et al, 1994;Luciano et al, 2003), gallbladder (Luciano & Real, 1969, 1990Nevalainen, 1977;Luciano et al, 1981), common bile duct (Riches, 1972;Luciano et al, 1981;Iseki, 1991), small and (Trier, 1963;Silva, 1966;Schofield, 1970;Nabeyama & Leblond, 1974;Tsubouchi & Leblond, 1979;Sugimoto et al, 1983;Trier et al, 1987;Gebhard & Gebert, 1999;Wille, 2001), and pancreatic duct (Weyrauch & Schnorr, 1976;Kugler et al, 1994;. Such cells have also been repo...…”
Section: Distribution Of Tuft Cellsmentioning
confidence: 99%
“…Tuft cells are present in the hollow organs of the digestive and respiratory tracts including the duct system of the salivary gland (Sato & Miyoshi, 1998a). They are characterized by long and blunt microvilli with prominent rootlets and by a well-developed tubulovesicular system in the supranuclear cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…1). In the rat submandibular gland, they constitute ∼4.8% of the duct wall (Sato and Miyoshi, 1998). The dark cells usually are narrow and contain an electron‐dense cytoplasm in which the basic organelles are sparse.…”
Section: Dark Cellsmentioning
confidence: 99%
“…The apical cytoplasm of SD cells in salivary glands of many species contains numerous small, ‘empty’‐appearing vesicles (Fig. 3A–C) [although in the rat submandibular gland they may contain fine filaments (Sato and Miyoshi,1998)]; a variety of functions has been suggested for them. By using tritium‐labeled fucose, (Hand 1979, 1987) demonstrated that at least some of these vesicles are involved in the transport of polysaccharides to the glycocalyx coating the apical surface of the duct cells and of membrane components to be incorporated into the apical plasmalemma.…”
Section: Clear Vesiclesmentioning
confidence: 99%
“…14) (Tandler et al, 1997c). Dark cells constitute 4.7% of the cells in the wall of the proximal EDs in the rat submandibular gland and 7.2% of the cells in the more distal EDs (Sato and Miyoshi, 1998). The nature of dark cells is unclear.…”
mentioning
confidence: 99%